Falsifikasi Popper dan Relevansinya pada Karakteristik Pembelajaran Mahasiswa; Andragogi dan Budaya Akademik - Rasya' Alfirdaus; Saffana Zahro Dinayah; Romi Dhia Ulhak; Winarto Winarto (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2024)
Philosophy is an integral part of science and is considered its parent. Philosophy and science have a close relationship, especially in the scientific context. The philosophy of science, with the framework of scientific theory, plays a role as a supporter of scholarly and scientific aspects and serves as the theoretical foundation in academic activities. Popper, a renowned philosopher, contributed the concept of falsification, emphasizing experimentation and criticism of scientific theories for the advancement of knowledge. In line with the goal of falsification, the progress and development of science are inevitable and need to be built. However, social facts indicate that scholarly discussion in student lectures is perceived as lacking vitality. The critical analytical attitude of students seems dormant. This issue diminishes the essence of andragogy and academic culture, which are essential characteristics of student education. Therefore, this article aims to address this problem by explaining and analyzing the learning process of students that prioritizes andragogy and academic culture in the context of their relevance to Popper's falsification concept. Thus, by understanding the points of relevance among these elements, the application of falsification can be better comprehended and implemented to achieve progress and development in scientific knowledge. In this literature-based article using a qualitative descriptive approach, the research findings conclude that there is a focal point on the development of students' critical reasoning in the interconnectedness of Popper's falsification, andragogy, and academic culture.Top of Form